Creating a Library Orientation Card Game to Reach New Transfer Students. Issue 1 (2nd January 2019) - Giles, Kelly; Shuyler, Kristen; Evans, Andrew; Reed, Jon
Abstract : Librarians and staff at a public university drew upon previous experience with instructional games to develop, implement, and assess a card game as a library orientation activity for new transfer students. This project was shaped by a desire to meet transfer students' unique needs as well as the logistical constraints associated with the university's transfer student orientation. The card game, modeled after Apples to Apples, presented information about the campus library system in a fun, informal way that allowed transfer students to socialize with each other while learning. Survey responses indicated that students found the game both enjoyable and helpful.